A Review of Adolescents’ Digital Self-Efficacy: Conceptualization, Measurement, Impacts, Influencing Factors, and Future Directions - Tan, Qing; Wu, Wenzhuo; An, Siying (Journal of Current Social Issues Studies, 2025)
With the deep penetration of digital technology in life and education, the cultivation of digital literacy among adolescents has become a focus. As a key component of digital literacy, digital self-efficacy profoundly affects adolescents’ use of digital systems and the development of digital competence. In this paper, we systematically review the current status of research on adolescents’ digital self-efficacy at home and abroad, elaborating on the evolution of its concept, the development of measurement tools, and analyzing its role in the use of digital systems and learning, as well as the influencing factors at the environmental and individual levels. At the same time, we point out the shortcomings of the current research in terms of conceptual connotation and structure, local characteristics, systematicity of influencing factors, formation and mechanism of action, and interventions, etc., and provide directions for the subsequent in-depth research, aiming to promote the development of the research on adolescents’ digital self-efficacy, and help to improve adolescents’ digital literacy.